Clinical epidemiological characterization of children with recurrent wheezing - Liudmila Nogueiras Batista; Pablo Antonio Hernández Dinza; Beatriz Reyes Hernández; Aimé Macia Quintosa; Niurbis Jiménez Portuondo (Centro Provincial de Información de Ciencias Médicas, 2021)
Introduction: The recurrent wheezing in infants and preschool children are frequent reason of visit in pediatrics.  Objective: To characterize children with recurrent wheezing from the clinical and epidemiologic points of view.  Methods: An observational, longitudinal and prospective investigation of 140 children with recurrent wheezing, assisted in the Respiratory Service  of Dr. Antonio María Béguez Cesar Southern Teaching Children Hospital was carried out  in Santiago de Cuba, from  January, 2016 to December, 2018.  Results: There was a prevalence of the male sex (57.1 %), the patients of urban origin (62.1 %) and 28 de Septiembre health area as that of more incidence (42.7 %). The average age was of 1 year and 5 months, approximately. The children included in the interval from 6 to 11 months and 29 days were the most affected (28.6 %). Among the municipalities, Guamá contributed the higher number of cases (33.9 %).  There was no statistical association between the prediction index of asthma and the sex; however, it was higher among males (19.3 %).  Conclusions: The clinical and epidemiologic characteristics of the patients with recurrent wheezing of this case material don't differ from the world epidemiologic context, being an entity of frequent observation in the pediatrics services.